2005
DOI: 10.1111/j.1364-3703.2005.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and stress adaptation by Mycosphaerella graminicola during sporulation in its host revealed through microarray transcription profiling

Abstract: SUMMARY Pathogenic microbes must successfully adapt to the host environment, acquiring nutrients and tolerating immune/defence responses. Studies on host-pathogen interactions at the transcriptome level have predominantly investigated host responses. Here we present a broad-scale transcriptional analysis on a fungal pathogen during sporulation within its host environment. Septoria leaf blotch is an important fungal disease of cultivated wheat and is caused by the ascomycete fungus Septoria tritici (teleomorph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…We chose the culture medium Czapek-Dox broth (CDB) as a defined medium that presents carbon as Suc and nitrogen as nitrate only, while a second medium, potato dextrose broth (PDB), presents a rich and complex variety of carbon and nitrogen sources. Both media support fungal growth via a form of yeastlike budding, which occurs approximately three to four times faster in PDB than in CDB (Keon et al, 2005). Five time points of leaf infection were selected to span key phases of the host-pathogen interaction (Fig.…”
Section: Identification and Classification Of Differentially Abundantmentioning
confidence: 99%
“…We chose the culture medium Czapek-Dox broth (CDB) as a defined medium that presents carbon as Suc and nitrogen as nitrate only, while a second medium, potato dextrose broth (PDB), presents a rich and complex variety of carbon and nitrogen sources. Both media support fungal growth via a form of yeastlike budding, which occurs approximately three to four times faster in PDB than in CDB (Keon et al, 2005). Five time points of leaf infection were selected to span key phases of the host-pathogen interaction (Fig.…”
Section: Identification and Classification Of Differentially Abundantmentioning
confidence: 99%
“…It is noteworthy that MgxLysM lacked any previous EST support (Keon et al, 2000(Keon et al, , 2005Kema et al, 2008) and contained a repeat sequence within intron 2 of the predicted gene model, albeit oriented on the opposite DNA strand (Table I). Each MgLysM protein contained variable numbers of Cys residues (ranging from five to nine), and Mg1LysM and MgxLysM were predicted to be significantly smaller proteins than Mg3LysM as a consequence of possessing fewer LysM domains.…”
Section: Identification Of Lysm Effector Homologs In the Genome Sequementioning
confidence: 99%
“…tritici Gene Expression-In order to investigate signaling networks activated in the fungus during its symptomless phase, we examined the expression of genes encoding fungal protein kinases (Slt2, Fus3, Hog1, and Tpk2), G protein (G␣3), and an ABC transporter (Atr4) in the infected hosts. It has been reported that S. tritici attempts to adapt to oxidative stress during the necrotrophic stage of infection through the high expression of genes implicated in stress tolerance (13,17), and a series of genes encoding CDWEs are uniquely expressed in planta compared with in vitro (15). Therefore, genes encoding an ROS-scavenging enzyme Cu 2ϩ /Zn 2ϩ superoxide dismutase and three CDWEs (arabinofuranosidase, xylanase, and glucosidase) were selected for gene expression analysis.…”
Section: Identification Of S Tritici Proteins and Phosphoproteins-mentioning
confidence: 99%
“…It remains in the apoplastic space to obtain nutrients throughout the entire infection cycle (14). So far, the transcriptome profiles of S. tritici in planta have been studied using microarray and expressed sequence tag library sequencing, focusing mainly on the necrotrophic phase because of the low fungal biomass at the biotrophic phase (10,(15)(16)(17). These studies revealed the expression of genes encoding cell-wall degrading enzymes (CDWEs) and genes involved in metabolism, transport, and signal transduction, such as MAPKs.…”
mentioning
confidence: 99%